2022
DOI: 10.3389/fimmu.2022.994699
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of CIRP by genetic factors of SP1 related to cold sensitivity

Abstract: Cold-inducible RNA-binding-protein (CIRP) is a cold shock protein that plays a protective role in genotoxic stress response. CIRP modulates inflammation in human diseases, inhibits cell proliferation, and protects cells from genotoxic damage during cellular stress. The mild cold responsive element and specificity protein 1 (SP1) play a role in Cirp expression at low temperatures. Although previous studies have provided insights into the immune functions of SP1 or CIRP, the mechanisms by which CIRP and SP1 me d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 57 publications
0
2
1
Order By: Relevance
“…[ 23 , 24 ] Furthermore, genetic factors related to cold sensitivity were founded in the latest study, they regulated expression and function of cold-inducible RNA-binding-protein in inflammatory response. [ 25 ] Although we did observe that individuals close to CH status had small negative stress responses to inadequate sleep, there were no clearly significant differences in inflammatory markers between the CH and non-CH groups. Further studies will be needed considering CH-related epigenetic processes in sleep disturbances.…”
Section: Discussioncontrasting
confidence: 53%
See 1 more Smart Citation
“…[ 23 , 24 ] Furthermore, genetic factors related to cold sensitivity were founded in the latest study, they regulated expression and function of cold-inducible RNA-binding-protein in inflammatory response. [ 25 ] Although we did observe that individuals close to CH status had small negative stress responses to inadequate sleep, there were no clearly significant differences in inflammatory markers between the CH and non-CH groups. Further studies will be needed considering CH-related epigenetic processes in sleep disturbances.…”
Section: Discussioncontrasting
confidence: 53%
“…[23,24] Furthermore, genetic factors related to cold sensitivity were founded in the latest study, they regulated expression and function of cold-inducible RNA-binding-protein in inflammatory response. [25] Although we did observe that individuals Table 2 Correlation between CH score and changes in each variable during sleep restriction and follow-up. close to CH status had small negative stress responses to inadequate sleep, there were no clearly significant differences in inflammatory markers between the CH and non-CH groups.…”
Section: Discussionmentioning
confidence: 72%
“… 15 Recently, a genome-wide association study (GWAS) of a population-based cohort suggested that the CIRP gene is associated with CP. 16 However, reports on genetic analysis with temperature sensitivity are still limited. Moreover, a GWAS in diverse cohorts is necessary for the discovery of candidate genes that lead to the disclosure of the genetic implications of temperature sensitivity.…”
Section: Introductionmentioning
confidence: 99%